2022
DOI: 10.3390/genes13101756
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Administration of PLX-R18 Cells Protects Mice from Radiation-Induced Hematopoietic Failure and Lethality

Abstract: Acute Radiation Syndrome (ARS) is a syndrome involving damage to multiple organs caused by exposure to a high dose of ionizing radiation over a short period of time; even low doses of radiation damage the radiosensitive hematopoietic system and causes H-ARS. PLacenta eXpanded (PLX)-R18 is a 3D-expanded placenta-derived stromal cell product designated for the treatment of hematological disorders. These cells have been shown in vitro to secrete hematopoietic proteins, to stimulate colony formation, and to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It is well known that the hematopoietic system is extremely sensitive to ionizing radiation. In earlier studies, we showed that various classes of prophylactic agents (PLX-R18, CDX-301, GT3, BBT-059, Ex-RAD, JNJ-26366821) were able to rescue mice from lethality by suppressing gamma radiation-induced damage in the hematopoietic system [14,15,17,24,25]. In this report, our data indicate that oral, prophylactic administration of PrC-210 provided equal or better protection of mice from radiation-induced lethality by protecting their hematopoietic system.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It is well known that the hematopoietic system is extremely sensitive to ionizing radiation. In earlier studies, we showed that various classes of prophylactic agents (PLX-R18, CDX-301, GT3, BBT-059, Ex-RAD, JNJ-26366821) were able to rescue mice from lethality by suppressing gamma radiation-induced damage in the hematopoietic system [14,15,17,24,25]. In this report, our data indicate that oral, prophylactic administration of PrC-210 provided equal or better protection of mice from radiation-induced lethality by protecting their hematopoietic system.…”
Section: Discussionmentioning
confidence: 52%
“…A clonogenic assay was performed with cells harvested from femoral bone marrow, as described previously [14]. Sternal histopathology was carried out on the sterna fixed in 10% neutral-buffered formalin, as described previously [17]. The bone marrow cellularity was qualitatively evaluated within the sternebrae, and megakaryocytes were counted by averaging the number of cells per 10 (40× high-powered fields (HPFs).…”
Section: Effect Of Prc-210 On the Bone Marrow Cellularity Post-tbimentioning
confidence: 99%